Manifestation Of Nihilism As A Destructive Social Phenomenon Of Society (Czech Journal of Multidisciplinary Innovations, 2024)
This article explores that nihilism emerged as a continuous social phenomenon in society in the history of human development, and often its interpretations are close to the fanatical spirit. Also, the author categorised the views of scholars who studied these processes